13C-NMR Spectrometric Identification of Acid Hydrolysed Hydroxypropyl Starch Components - Haryadi Haryadi (agriTECH, 1991)
The products of acidic hydrolysis of hycroxypropyl starch (molar substitution 0.28) were isolated by HPLC using an amine treated μ Poracilcoloumn. Based on the 13C-NMR Spectral data the Individual fractions were assigned 1,2-0-[1.2-(S)-propyiene]-a-Dglucofuranose, 12-0-[1 ,2-(R) and (S)-propylene]-a-D-glucopyranose, 2-0-[2-hydroxypyl-(R) and (S)]-α,B-D-glucopyranose, and 6-0-[2-(R) and (S)-hydroxypropyI]-α,B-D-glucopyranose, respectively.